2022
DOI: 10.1155/2022/6085515
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Curcumin against Doxazosin- and Carvedilol-Induced Oxidative Stress in HepG2 Cells

Abstract: Doxazosin and carvedilol have been evaluated as an alternative treatment against chronic liver lesions and for their possible role during the regeneration of damage caused by liver fibrosis in a hamster model. However, these drugs have been reported to induce morphological changes in hepatocytes, affecting the recovery of liver parenchyma. The effects of these α/𝛽 adrenoblockers on the viability of hepatocytes are unknown. Herein, we demonstrate the protective effect of curcumin against the possible side effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…As shown by previous studies, the level of toxicity caused by doxazosin in cells varies from cell to cell. For example, HepG2 cell viability remained about 80% after treatment with 15 µ m doxazosin for 24 h, whereas about 60% of the HepG2 cells lost vitality after treatment with 25 µ m doxazosin for 24 h. [ 34 ] Similarly, after treatment with 30 µ m doxazosin for 24 h, about 78% of the PC‐3 cells were viable. [ 17 ] In this study, we examined the pharmacotoxicity of doxazosin in HUVECs and HHSECs and found that the drug toxicity increased with increasing concentrations of doxazosin.…”
Section: Discussionmentioning
confidence: 99%
“…As shown by previous studies, the level of toxicity caused by doxazosin in cells varies from cell to cell. For example, HepG2 cell viability remained about 80% after treatment with 15 µ m doxazosin for 24 h, whereas about 60% of the HepG2 cells lost vitality after treatment with 25 µ m doxazosin for 24 h. [ 34 ] Similarly, after treatment with 30 µ m doxazosin for 24 h, about 78% of the PC‐3 cells were viable. [ 17 ] In this study, we examined the pharmacotoxicity of doxazosin in HUVECs and HHSECs and found that the drug toxicity increased with increasing concentrations of doxazosin.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has often been reported to exhibit a direct antioxidant capacity, which can relieve oxidative stress by scavenging ROS [32,33]. These could be attributed to the chemical structure of curcumin; a lipophilic polyphenol with a conjugated double bond serves as a powerful electron donor to inhibit the redox processes that produce ROS [34,35]. Thus, curcumin could improve the antioxidant capacity of broiler chickens infected with Coccidioides and maintain the equilibrium of the antioxidant enzyme system.…”
Section: Discussionmentioning
confidence: 99%